Um sistema de recomendação para reparação de erosão arquitetural de software = A recommendation system for repairing software architecture erosion - Ricardo Terra Nunes Bueno Villela (2013)
Architectural erosion is a recurrent problem faced by software architects. Although several architecture conformance techniques have been proposed to detect architectural violations (e.g., reflexion models, dependency structure matrices, source code query languages, constraint languages, architecture description languages, and design tests), less research effort has been dedicated to the task of repairing such violations. As a consequence, developers usually perform the repairing task in ad hoc ways, without tool support at the architectural level. This fact may lead developers to spend a long time to discover how to repair the architectural violations and even to introduce new violations when repairing one. In view of such circumstances, this thesis proposes an architectural repair recommendation system that provides fixing guidelines for developers and maintainers when tackling architectural erosion. We have formalized a catalog of repairing recommendations to repair violations raised by static architecture conformance checking approaches; we have elaborated a suitable module heuristic to determine the correct module for source code entities; we have designed a toolcalled ArchFixthat triggers the proposed recommendations; and we have evaluated the application of our approach in two industrial-strength systems. For the first systema 21 KLOC open-source strategic management systemour approach indicated correct repairing recommendations for 31 out of 41 violations detected as the result of an architecture conformance process. For the second systema 728 KLOC customer care system used by a major telecommunication companyour approach triggered correct recommendations for 632 out of 787 violations, as asserted by the systems architect. Moreover, the architects scored 80% of these recommendations as having moderate or major complexity.